Устройство для подъема затонувшего объекта - Барсуков В. Д. Виталий Дементьевич; Голдаев С. В. Сергей Васильевич; Зима В. П. Владислав Павлович; Рыбасова Н. Л. Наталья Леонидовна; Трунов А. А. Андрей Анатольевич; Чумаров Р. И. Рудольф Иванович
опубл. 30.04.92